TRANSFORMASI IDENTITAS DALAM ARSITEKTUR INTERIOR MASJID RAMLIE MUSOFA: SINERGI BUDAYA DAN SPIRITUALITAS: IDENTITY TRANSFORMATION IN THE ARCHITECTURE INTERIOR OF RAMLIE MUSOFA MOSQUE: A SYNERGY OF CULTURE AND SPIRITUALITY - Layla Nurina Kartika Iskandar; Siti Febrina Rahmadani; Rosalinda Wiemar; Ariani (Universitas Trisakti, 2026)
The Ramlie Musofa Mosque, located at Jalan Danau Sunter Selatan Blok I/10 No.12C-14A, North Jakarta, serves as a fascinating example of cultural acculturation in mosque architecture in Indonesia. The research titled